Social Relations And Community Response To River Water Pollution In Batang Arau Village, Padang Selatan Subdistrict, Padang City, West Sumatra Province - Irwan, Irwan; Nurariyanti, Lisa; Agustina, Nadia; Nahdiati, Nahdiati (International Journal of Economics (IJEC), 2025)
This study aims to analyze social relations and community responses due to river water pollution in Batang Arau Village, Padang Selatan District, Padang City, West Sumatra Province. This study uses the social construction theory of Peter L. Berger and Thomas Luckman, namely that reality is formed socially and social reality as a process through human actions and interactions. Social reality is not objective or independent, but is the result of construction through social interaction. This study uses a qualitative approach with a descriptive research type. Data collection methods are carried out by document studies, non-participant observations and in-depth interviews. Data analysis using the Milles and Huberman (1992) model which is carried out in several stages, namely data collection, data reduction, data presentation, and drawing conclusions. Based on the results of the study, it can be concluded that in social relations of the community due to water pollution of the Batang Arau River, there is a conflict between communities living around the river where people who are less concerned about the cleanliness of the river water throw garbage carelessly into the river so that other people feel disturbed because of the impacts caused such as garbage scattered on the banks of the river and even causing flooding when it rains. The community's response to water pollution of the Batang Arau River is first, reminding each other not to throw garbage into the river. Second, the community adapts or adjusts to river water pollution, which used to use river water for bathing and washing then switched to using drilled wells, rainwater that is collected to do activities such as bathing or washing. Third, the community strongly supports the efforts made by the government to deal with the problem of water pollution in the Batang Arau River